Fundamental attitudes of the Russian political elite: Law, truth, public welfare and violence - Susan Stewart (Stiftung Wissenschaft und Politik (SWP), 2017)
This study examines behavioural patterns of the top echelons of Russia's elite within four fundamental spheres (law, truth, public welfare and violence) since 2008 and discovers certain continuities. It reveals the elite's fundamental attitudes in the four areas as evinced by its actions - attitudes which will have a decisive impact on German-Russian and EU-Russia relations in the future. The study shows that Russia's actions since 2014 - which have surprised many Western observers - are based on attitudes that were already perceptible before then. These attitudes can thus be considered part of the Russian elite's long-standing political culture. Today, it is the instrumentalisation of law, truth and violence in foreign and domestic politics, and a desire for control derived from mistrust in external and internal actors, that especially characterise Russia's elite. The common good or well-being of the Russian people is not a priority for the elite, or only in purely instrumental terms. Politicians and policymakers in Germany and the EU need to take these fundamental attitudes into account when developing a medium- to long-term approach to Russia because they will shape the actions of numerous members of the Russian elite for the foreseeable future.
Keywords: 320